Instagram Marketing Boosts Sales for Small Businesses: Pemasaran Instagram Meningkatkan Penjualan untuk Bisnis Kecil - Rahmah, Fiqih Arina; Rochmaniah, Ainur (Universitas Muhammadiyah Sidoarjo, 2024)
This study explores the utilization of Instagram as a promotional tool for Dhe Gedangku, a small-scale microbusiness in Gempol District. Through qualitative descriptive analysis and case study method, data were gathered from in-depth interviews with the owner and followers of @dhegedangkuofficial. Findings reveal that Instagram significantly increases product awareness and sales, with a 45% sales increase noted. However, there is a gap in maximizing product promotion, particularly in terms of innovation and packaging. Dhe Gedangku offers products at affordable prices, targeting students and young adults, and utilizes strategic location selection and Instagram's geo-tagging feature to attract customers. The study underscores the importance of businesses focusing on innovation, packaging, pricing strategies, and strategic location selection to maximize Instagram's potential in marketing small businesses, offering insights for businesses seeking to enhance their social media marketing strategies. Hightligh: Instagram Promotion: Boosts sales and product visibility for small businesses. Affordable Pricing: Targets students and young adults with budget-friendly prices. Strategic Location: Uses geo-tagging to attract customers to small business locations. Keywords: Instagram, Small Business, Promotional Tool, Social Media Marketing, Microbusiness